2019
DOI: 10.1016/j.ipej.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Late elimination of challenging idiopathic ventricular arrhythmias originating from left ventricular summit by anatomical ablation

Abstract: Ablation of premature ventricular complexes (PVCs) originating from left ventricular outflow tract (LVOT)/left ventricular summit (LVS) is challenging with considerable rate of failure. Recently, in a novel approach to ablation of these arrythmias, application of radiofrequency energy to anatomically opposite sites of presumed origin of arrythmia, has been associated with moderate procedure success. Although late elimination of PVCs that are persistent following an ablation procedure has been previously report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have reported the utility of the anatomic approach in RF catheter ablation of VAs. [16][17][18] However, in all or almost all cases in those studies, [16][17][18] As shown in this study, there is a possibility that the QRS morphology of a VA originating from the posterior RVOT changes during catheter ablation procedures. 15,[19][20][21] Therefore, a detailed and continuous observation of the QRS morphology is important during the ablation to identify the changes in the QRS morphology.…”
Section: Previous Studiesmentioning
confidence: 62%
See 1 more Smart Citation
“…Previous studies have reported the utility of the anatomic approach in RF catheter ablation of VAs. [16][17][18] However, in all or almost all cases in those studies, [16][17][18] As shown in this study, there is a possibility that the QRS morphology of a VA originating from the posterior RVOT changes during catheter ablation procedures. 15,[19][20][21] Therefore, a detailed and continuous observation of the QRS morphology is important during the ablation to identify the changes in the QRS morphology.…”
Section: Previous Studiesmentioning
confidence: 62%
“…Previous studies have reported the utility of the anatomic approach in RF catheter ablation of VAs 16–18 . However, in all or almost all cases in those studies, 16–18 the clinical VAs had characteristic ECG findings of a left‐sided origin, and the earliest activation time was found in the left‐sided OT before the ablation. Therefore, from the beginning, mapping was started from the left‐sided OT, and, in most cases, catheter ablation was performed only in the left‐sided OT.…”
Section: Discussionmentioning
confidence: 94%
“…The superior portion of LVS is dangerous for pericardial penetration. It increases the risk of major and minor complications, such as intrapericardial bleeding, coronary artery stenosis, delayed tamponade and incidental right ventricle puncture [85][86][87][88][89]. Table 1 summarizes possible approaches to the LVS area.…”
Section: Lvs Accessibility and Ablationsmentioning
confidence: 99%